To study the outcome of previous one cesarean pregnancies in a rural tertiary center of Haryana, India - S., Siwach; P., Lakra; V., Sangwan; Shivani, .; R., Kansal; R., Mahendru (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Rising rates of caesarean section is a matter of great concern and TOLAC is an attractive alternative. Analysing outcome of previous one caesarean pregnancies will provide an insight for reducing the caesarean rates and formulating protocols and policies for TOLAC. Methods: A retrospective study of patients of previous one caesarean pregnancy was done from February 2015 to January 2016 and 3 groups were made, ERCS group, failed TOLAC group and successful TOLAC group. The rates of elective repeat caesarean, failed TOLAC, successful TOLAC, maternal complications, neonatal morbidity and mortality in all three groups were studied. Results: There were 5177 total deliveries with 488 (9.43%) previous one caesarean pregnancies. Out of 488 patients 161 (33%) underwent elective repeat caesarean and 327 (67%) underwent trial of labour. Out of 327 patients 234 (71.56%) had a successful TOLAC and 93 (28.44%) had failed TOLAC. Breech (23%) followed by foetal distress (20%) were the most common indications of previous caesarean. Commonest indication of elective repeat caesarean was short interval (33%) and that of failed TOLAC was foetal distress (38.7%) followed by failed induction (23.6%). There were 4 morbidly adherent placentas (0.82%), 1 scar rupture, 3 scar dehiscence, no maternal mortality and 10 neonatal deaths. Conclusions: Previous one caesarean section is not only a risk factor for repeat caesareans and complications like morbidly adherent placenta, uterine rupture but also a financial burden on health facilities. Encouraging the patients for trial of labour and emphasizing the usage of contraception is the need of the hour.